Determinants of Capabilities Among Chronically Mentally Ill People: A Path Model. (July 2020) - Baumgardt, Johanna; Röh, Dieter; Daubmann, Anne
Background: In the context of political demands for social justice, we analyzed determinants of capabilities in community-based clinical social work. Within the scope of an explorative study with two measuring points, people with chronic mental disorders were questioned regarding capabilities as well as psychosocial, sociodemographic, disease-, and care-related aspects in community mental health-care services in Germany. Results: Overall, capabilities were rated as medium and did not change significantly over time. A path model showed empowerment and social inclusion to be the strongest determinants on the improvement of capabilities. Conclusion: Community-based clinical social work should foster empowerment and social inclusion through socio-therapeutic or, rather, psychosocial interventions in order to alter capabilities among chronically mentally ill people. This could include psycho- or socio-education as well as family interventions that aim to reduce stress in the family or training in life skills such as dealing with money, personal hygiene, or communication competencies.